Aktivitas Antibakteri Ekstrak n-Heksan, Etil Asetat, dan Etanol 70% Daun Binahong (Anredera cordifolia (Ten.) Steen) terhadap Pseudomonas aeruginosa ATCC 27853 - Dyah Susilowati; Putri Manggara Mitha (Fakultas Farmasi Universitas Setia Budi, 2009)
Binahong leaf (Anredera cordifolia (Ten.) Steen) are type of crops which good to heal some kinds of diseases. Binahong leaf contains the saponin, flavonoid, and polifenol. This research aim to know the antibacterial activity of n-heksan extracts, ethyl acetate and etanol 70 % from Binahong leaf that most effective to Pseudomonas aeruginosa ATCC 27853. Binahong leaf powder high rise soxhleted by n-heksan, ethyl acetate, and etanol 70 % solvent. Jell extracts of n-heksan, ethyl oacetate and etanol 70 % extract obtained were tested of antibacterial activity by 2 methods and made with concentration 100 % (b/v); 50 % (b/v); 25 % (b/v); 12,5 % (b/v); 6, 25 % (b/v); 3,125 % (b/v); 1,56 % (b/v); 0,78 % (b/v); 0,39 % (b/v); and 0,195 % (b/v) to antibacterial activity test by dilution method. Diffusion method conducted by made of well that have diameter 9 mm, then dripped with n-heksan extracts, ethyl acetate and etanol 70 % with concentration 25 %; 50 %; 75 %; 100 %; and blanco each counted 40 Âµl, then measured by its resistance diameter. Experiment result of antibacterial activity test Pseudomonas aeruginosa ATCC 27853, ethyl acetate and etanol 70 % extracts has KBM 50 % (b/v) dan 25 % (b/v), while n-heksan extracts do not give KBM. Research result of diffusion method give the resistance area by mean of acetate ethyl extracts 8,33 mm (75 %); 11,67 mm (100 %) and for the etanol 70 % extracts 9,67 mm (50 %); 12,67 mm (75 %); 15,33 mm (100 %) while for the of n-heksan extracts do not give the resistance area. So can be concluded that etanol 70 % extracts more effective as antibacterial to Pseudomonas aeruginosa ATCC 27853 than n-heksan and ethyl acetateextracts.